Voices of discomfort: metaphorical conceptualisations of physical pain in Algerian Arabic - Rababah, Ghaleb; Nesba, Kaouther; Alghazo, Sharif; Abusalim, Nimer; Rayyan, Mohammad (Frontiers in Communication, 2024)
This study probes the metaphorical representations of physical pain among Algerian Arabs. To unearth these conceptualisations, an oral Discourse Completion Test (DCT) was administered to 30 Algerian university students. Grounded in Kövecses' ( 2006) model of metaphorical conceptualisations, this research unveils that Algerian Arabs utilise nine distinct metaphorical expressions when portraying physical discomfort. These encompass evaluative metaphors, fire metaphors, sharp object metaphors, container metaphors, animal metaphors, creeping insect metaphors, burden metaphors, swing metaphors, and physical force metaphors. This exploration sheds light on the intricate weave of metaphors in Algerian Arabic, underscoring their pivotal role in encapsulating emotional experiences. It also beckons further scholarly inquiries into the manifold metaphorical renderings of diverse emotional states across Arab communities.